Flight of the Moon Dragon - West, Tracey, 1965-; Jones, Damien (New York : Branches/Scholastic Inc., 2016)
The prime Dragon Stone seems to be dying, and that means that the connection between the dragon masters and their dragons is also fading, so the six dragon masters must locate the hidden stone, and learn what is causing the problem before their telepathic connection is completely gone.
480
Keywords: Dragons -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Fantasy fiction